Surface patterning using speckle lithography for sers application - Low, Zheng Ying (Nanyang Technological University, 2024)
Laser speckles, a phenomenon caused when a laser reflects diffusely of a surface forming a granular pattern, is long considered as undesirable noise. In this project, the laser speckle effect is utilized to perform lithography to fabricate scattering substrates. Speckle lithography takes advantage of the laser speckles to form the target pattern, eliminating the use of an optical mask in conventional lithography. Initial simulations in ANSYS Lumerical were carried out to understand the effect of surface roughness in light localization. The simulations displayed a clear trend of increasing electric field intensity with increasing surface roughness. Optimization of the experimental parameters were then carried out by varying exposure time and power. Speckle patterns of different sizes were created by varying the laser spot size at the diffuser. The fabricated patterned surfaces are then used in Raman spectroscopy to test its effectiveness as SERS substrate. The results of the Raman spectroscopy confirm the findings from the simulations, where having higher surface roughness increases the intensity of Raman signals. This project gives insight into the ability of speckle lithography to fabricate scattering substrates over conventional lithography